FTC Based Pre-Extension Demonstration of Tef Varieties in East and North Showa, Ethiopia - Mekuriaw, Truayinet (International Journal For Research In Agricultural And Food Science, 2022)
The objectives of this on-farm demonstration were to create awareness on the availability and importance of the new tef varieties and to create wider demand pull by reaching large number of users over relatively wider geographical area. In addition to this the study aimed to enhance institutional and functional linkages with key players through joint actions and performances. Training and experience sharing events like field days were used to demonstrate the new improved tef varieties. For the on-farm demos seeds of the newly released varieties were provided to farmers at the rate of 10 kg/ha on a revolving seed loan basis. The plot size was 10 m x10 m at all locations. Training on agronomic practices (land preparation, sowing, weeding, harvesting and post-harvest handling) was given for farmers and experts by experienced researchers from respective departments. Farmer together with researchers and agricultural experts periodically evaluated the performance of each variety during group visit. Data were collected through field observation and direct measurements. A field day was organized at maturity stage at all three sites Lume, Adea and Minjar-shenkora and a total of 816 participants (760 male and 56 females) were participated on the event. All the demonstrations were perform well at each site and great awareness has been created on the availability and importance of the new tef varieties. In addition, good institutional linkages were established among the partners including district and zonal agriculture offices, seed producer companies and seed producing farmer cooperatives. This study recommend that, on-farmer and farmers’ training center (FTC) based demonstrations of improved new tef varieties would greatly enhance adoption and thereby production and productivity of tef along with minimizing the risks of failures of the newly released varieties at on farm level. Working in collaboration with zonal and district agriculture offices and seed producers proved useful for the sustainability of new improved varieties in production.